Development and Elucidation of Superior Turnover Rates and Selectivity of Supported Molecular Catalysts. Issue 8 (6th February 2018) - Ye, Rong; Liu, Wen‐Chi; Han, Hui‐Ling; Somorjai, Gabor A.
Abstract: Supported molecular catalysts consist of nanomaterials immobilized on a solid support. Important factors that control catalyst properties (reactivity, product selectivity, and stability) include the structure and compositions of both nanomaterials and supports. This review focuses on recent studies of supported molecular catalysts with controlled activity and selectivity in our group. We will first introduce the development of previously unexplored supported molecular catalysts. We will demonstrate the controllable selectivity of catalysts based on acidified mesoporous silica, metal‐organic frameworks (MOFs), hydrogen‐activated tungsten oxides, and noble metal doped Mn x O y /Na2 WO4 catalyst supported on mesoporous silica. We will then discuss advanced characterization techniques under reaction conditions, which offer mechanistic explanations of activity and selectivity of supported molecular catalysts. The applications of chemical transient kinetics (CTK) analysis, ambient pressure X‐ray photoelectron spectroscopy (APXPS), and sum‐frequency generation vibrational spectroscopy (SFG‐VS) are discussed. Next, we will describe new insights into catalysis at the nanoparticle‐support interfaces, which are catalytic environments unique to supported molecular catalysts. Examples include reactions at oxide‐metal interfaces and alcohol oxidation reactions at solid–gas and solid–liquid interfaces. Lastly, we will discuss heterogenized homogeneous catalysts and heterogenized enzyme catalysts as future directions of supported molecular catalysts. Abstract : Elucidate, eliminate, characterize : Nanomaterials including nanoparticles, enzymes, and clusters are loaded into MOFs, metal oxides, or aluminosilicates to form supported molecular catalysts. Other than ex situ studies, these catalysts are investigated by sum frequency generation vibrational spectroscopy, ambient pressure X‐ray photoelectron spectroscopy, and chemical transient kinetics under reaction conditions.